JUST LIKE BLACK, ONLY BETTER: POOR WHITE IN ANTEBELLUM SOUTH OF AMERICA DEPICTED IN SOLOMON NORTHUP'S NOVEL TWELVE YEARS AS A SLAVE - Rasiah, Rasiah; Putra, Ansor; Masri, Fina Amalia; Arman, Arman; Pardilla, Suci Rahmi (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2021)
(Title: Just Like Black, Only Better: Poor White in Antebellum South of America Depicted in Solomon Northup's Novel